World without walls II - Wong, Ayman Rashdan (Patriots Publication Sdn Bhd, 2020)
The world is facing major changes that is known as the collapse of the liberal world order. The integrity of the international system built by the United States since 1945 based on liberal democracy, market economy and human rights are now facing great challenges from the rise of the leaders "strongman", economic protectionism and nationalist-populist spirit. What is happening to the globalization and borderless world that have aggressively been circulated in the last three decades? Is the new world order that will be born later would be better than the old order, or otherwise? By using these three main keys of geopolitics, which are POWER, GEOGRAPHY and IDENTITY, this book will elaborate on the major questions regarding the current international relations.